All-inside anterior cruciate ligament reconstruction with and without anterolateral ligament reconstruction: a prospective study - Ali Torkaman; Mehdi Hosseinzadeh; Elham Mohammadyahya; Parsa Torkaman; Mohammad Reza Bahaeddini; Amir Aminian; Hamed Tayyebi (BMC Musculoskeletal Disorders, 2024)
Abstract Background There is no clear consensus regarding the superiority of a combined anterior cruciate ligament reconstruction (ACLR) with anterolateral ligament reconstruction (ALLR) versus an isolated ACLR. In this study, we compared the postoperative stability profile, complications, and patient-reported outcomes of these procedures. Methods Twenty-one patients with an anterior cruciate ligament (ACL) tear who were either treated by an isolated all-inside ACLR (n = 21) or a combined all-inside ACLR and ALLR (n = 20) were included. The outcomes were evaluated in the last follow-up and included the postoperative stability profile evaluated by the Lachman test, pivot shift test, and KT-1000 side-to-side difference, postoperative complications, and patient-reported outcomes evaluated by the International Knee Documentation Committee (IKDC) score and Lysholm knee scale. Results The baseline characteristics of the two groups were not significantly different. The residual Lachman and pivot shift were not significantly different between the two groups (P = 0.41 and P = 0.18, respectively). The mean KT-1000 side-to-side difference was 1.93 ± 1.9 mm in the isolated and 1.635 ± 0.91 mm in the combined group (P = 0.01). The mean improvement of the IKDC score was not significantly different between the isolated and combined groups (24.7 vs. 25.2, P = 0.28). The mean improvement of the Lysholm scale was not significantly different between the isolated and combined groups (33.5 vs. 34.1, P = 0.19). ACL re-rupture occurred in three patients of the isolated group and no patient of the combined group. Conclusion The outcomes of patients in the present study support performing a combined ALL and ACL reconstruction.